(untitled) (Research, Society and Development, 2020)
Odontoma is a benign odontogenic tumor of epithelial and mesenchymal origin, often associated with embedded teeth, dental germs or supernumerary teeth. A classification of odontoma is based on its morphology and can be evaluated as a compound when it has multiple denticles. Treatment consists of surgical excision of the tumor, preserving the related dental units. Therefore, this study aims to report a surgical approach to an odontoma composed by means of a descriptive, qualitative, case report type. Female patient, 13 years old, with tomographic examination showing radiopaque mass structures similar to teeth incorporated in the region of tooth 43. On physical examination, she presented a slight increase in volume in the 43 lingual region, causing dental crowding. The proposed treatment was enucleation and curettage under local anesthesia. The patient returned to the outpatient clinic OMFS after 8 months with panoramic radiography suggesting new bone formation in the region of tooth 43 and without clinical and radiographic signs of lesion recurrence. Thus, odontomas are tumors usually diagnosed in routine radiographic examinations and can be associated with dental retention and crowding. The treatment of choice consists of surgical excision through enucleation associated with curettage, with a low recurrence rate.